2006
DOI: 10.1111/j.1365-3059.2006.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of molecular‐based diagnosis for ‘Candidatus Liberibacter asiaticus’, the causal pathogen of citrus huanglongbing

Abstract: Conventional PCR and two real-time PCR (RTi-PCR) methods were developed and compared using the primer pairs CQULA03F/CQULA03R and CQULA04F/CQULA04R, and TaqMan probe CQULAP1 designed from a speciesspecific sequence of the rplJ/rplL ribosomal protein gene, for diagnosis of citrus huanglongbing (HLB) disease in southern China. The specificity and sensitivity of the three protocols for detecting ' Candidatus Liberibacter asiaticus' in total DNA extracts of midribs collected from infected citrus leaves with sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 15 publications
1
77
0
1
Order By: Relevance
“…The amount of DNA obtained from the lysis was estimated using electrophoresis, with known concentrations of standard fragments of the vector pGEM ® 3Zf (+) (supplied by Applied Biosystems) as a control. The quantification of CLas based on copy number (CN) of the target gene was done as described by Wang et al (2006). The plasmid solution was serially diluted ten-fold from 10 ngµl −1 (2.1×10 9 CN) to 0.01 fgµl −1 (7×10 1 CN), and the Q-PCR assay was run by adding at each dilution point 100 ng of total DNA from healthy citrus plants.…”
Section: Standard Curvementioning
confidence: 99%
See 2 more Smart Citations
“…The amount of DNA obtained from the lysis was estimated using electrophoresis, with known concentrations of standard fragments of the vector pGEM ® 3Zf (+) (supplied by Applied Biosystems) as a control. The quantification of CLas based on copy number (CN) of the target gene was done as described by Wang et al (2006). The plasmid solution was serially diluted ten-fold from 10 ngµl −1 (2.1×10 9 CN) to 0.01 fgµl −1 (7×10 1 CN), and the Q-PCR assay was run by adding at each dilution point 100 ng of total DNA from healthy citrus plants.…”
Section: Standard Curvementioning
confidence: 99%
“…Li et al (2006) reported a Q-PCR assay capable of detecting and quantifying the three species of Liberibacter (africanus, asiaticus, and americanus). Wang et al (2006) reported a Q-PCR assay detecting CLas and a method for estimating the copy number of a cloned Liberibacter gene as an indirect measure of bacterial populations in plants. We have also previously developed a Q-PCR assay based on the TaqMan system and the 16S rDNA genomic sequences of CLas as a template (Carlos et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome analysis has been used to successfully identify how Las infection influences gene expression in citrus plants on a global scale. 9,32,33 In particular, extensive changes in gene expression were identified for major biological processes such as stress responses, signal transduction, transport, cell organization and carbohydrate metabolism. 34 From a bacterial prospective, several proteins have been identified as important for virulence and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of the plasmid DNA based on the copy number (CN) of the target gene was determined as previously described by Wang et al (2006). The plasmid solution was serially diluted from 10 8 CN to 1 CN.…”
Section: Dna Sample and Plasmid Preparationmentioning
confidence: 99%